2022
DOI: 10.22495/cgobrv6i1p3
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional impacts of governance on economic growth: Panel data evidence from the emerging market

Abstract: In a modern economy, good governance is considered a prominent factor for economic growth (Liu, Tang, Zhou, & Liang, 2018). However, Sub-Saharan Africa has a poor track record of good governance and economic growth (Fayissa & Nsiah, 2013). Therefore, this study is aimed to investigate the impact of governance on economic growth in Sub-Saharan Africa. Panel data that covers a period from 2005 to 2019 for 34 countries and the principal component analysis (PCA) method are employed to achieve the stated ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The results showed the impact of public sector governance on economic growth. This result agrees with a study by Feyisa et al (2022), so countries must focus on activating the principles of public sector governance in their institutions to raise their economic growth rates, whereas the results also showed a negative impact of starting a business on economic growth and this agrees with the results of a study by Attia et al (2017).…”
Section: Discussion Of Conclusion and Recommendationssupporting
confidence: 92%
See 3 more Smart Citations
“…The results showed the impact of public sector governance on economic growth. This result agrees with a study by Feyisa et al (2022), so countries must focus on activating the principles of public sector governance in their institutions to raise their economic growth rates, whereas the results also showed a negative impact of starting a business on economic growth and this agrees with the results of a study by Attia et al (2017).…”
Section: Discussion Of Conclusion and Recommendationssupporting
confidence: 92%
“…The study Feyisa et al (2022) verified the extent to which governance affects economic growth in Africa, during the period 2005-2019. Through the use of the main component analysis method (PCA), the study found a positive impact of governance indicators (corruption control, government effectiveness, organizational quality and rule of law) on the real total (economic growth), whereas the indicators political stability, absence of violence and voice and accountability turned out to be unimportant in statistical analysis.…”
Section: Studies Examine the Relationship Between Governance And Econ...mentioning
confidence: 56%
See 2 more Smart Citations
“…The scholars [17] also assess the impact of public administration factors on economic growth, and similarly to this study, build econometric models using panel data. However, in their study, the authors supplement the analysis by using the principal component method.…”
Section: Resultsmentioning
confidence: 99%